Characterization and Genomic Analysis of Fererhizobium litorale gen. nov., sp. nov., Isolated from the Sandy Sediments of the Sea of Japan Seashore - Lyudmila Romanenko; Nadezhda Otstavnykh; Naoto Tanaka; Valeriya Kurilenko; Vasily Svetashev; Liudmila Tekutyeva; Valery Mikhailov; Marina Isaeva (Microorganisms, 2023)
The taxonomic status of two gram-negative, whitish-pigmented motile bacteria KMM 9576T and KMM 9553 isolated from a sandy sediment sample from the Sea of Japan seashore was defined. Phylogenetic analysis revealed that strains KMM 9576T and KMM 9553 represent a distinct lineage within the family Rhizobiaceae, sharing 100% 16S rRNA sequence similarity and 99.5% average nucleotide identity (ANI) to each other. The strains showed the highest 16S rRNA sequence similarities of 97.4% to Sinorhizobium garamanticum LMG 24692T, 96.9% to Ensifer adhaerens NBRC 100388T, and 96.8% to Pararhizobium giardinii NBRC 107135T. The ANI values between strain KMM 9576T and Ensifer adhaerens NBRC 100388T, Sinorhizobium fredii USDA 205T, Pararhizobium giardinii NBRC 107135T, and Rhizobium leguminosarum NBRC 14778T were 79.9%, 79.6%, 79.4%, and 79.2%, respectively. The highest core-proteome average amino acid identity (cpAAI) values of 82.1% and 83.1% were estimated between strain KMM 9576T and Rhizobium leguminosarum NBRC 14778T and ‘Rhizobium album’ NS-104, respectively. The DNA GC contents were calculated from a genome sequence to be 61.5% (KMM 9576T) and 61.4% (KMM 9553). Both strains contained the major ubiquinone Q-10 and C18:1ω7c as the dominant fatty acid followed by 11-methyl C18:1ω7c and C19:0 cyclo, and polar lipids consisted of phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, an unidentified aminophospholipid, and two unidentified phospholipids. Based on phylogenetic and phylogenomic analyses, and phenotypic characterization, strains KMM 9576T and KMM 9553 are concluded to represent a novel genus and species, for which the name Fererhizobium litorale gen. nov., sp. nov. is proposed. The type strain of the type species is strain KMM 9576T (=NRIC 0957T).